Iron-catalyzed domino Knoevenagel-hetero-Diels–Alder reaction: facile access to oxabicyclo[3.3.1]nonene derivatives. Issue 23 (28th May 2019) - Wu, Mingchang; Yang, Junhang; Luo, Fang; Cheng, Cungui; Zhu, Gangguo
Abstract : An iron-catalyzed domino Knoevenagel-hetero-Diels–Alder reaction has been developed. Abstract : A Fe-catalyzed domino Knoevenagel-hetero-Diels–Alder reaction of alkenyl aldehydes and 1, 3-diketones has been developed. It provides straightforward access to a series of oxabicyclo[3.3.1]nonene derivatives in promising yields with excellent diastereoselectivity and functional group tolerance. The resultant bridged dihydropyrans can be smoothly converted into chromene derivatives, thus highlighting the synthetic utility of this method.